2011
DOI: 10.1111/j.1600-0668.2010.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation rates and health: multidisciplinary review of the scientific literature

Abstract: Ventilation with outdoor air plays an important role influencing human exposures to indoor pollutants. This review and assessment indicates that increasing ventilation rates above currently adopted standards and guidelines should result in reduced prevalence of negative health outcomes. Building operators and designers should avoid low ventilation rates unless alternative effective measures, such as source control or air cleaning, are employed to limit indoor pollutant levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
384
2
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 585 publications
(399 citation statements)
references
References 45 publications
5
384
2
8
Order By: Relevance
“…The results indicated that low ventilation rates in classrooms significantly reduce pupils' attention and vigilance, and negatively affect memory and concentration. In another study, Sundell et al (2011) stated that higher ventilation rates in offices, up to about 25 l/s per person, are associated with reduced prevalence of SBS symptoms, whereas the state of having lower ventilation rates contributes to causing symptoms such as inflammation, respiratory infections, asthma symptoms and short-term sick leave. Additionally, sufficient use of natural ventilation (NV) systems can be also considered as a promising strategy to tackle the SBS.…”
Section: Sbs Contributors Symptoms and Effectsmentioning
confidence: 99%
“…The results indicated that low ventilation rates in classrooms significantly reduce pupils' attention and vigilance, and negatively affect memory and concentration. In another study, Sundell et al (2011) stated that higher ventilation rates in offices, up to about 25 l/s per person, are associated with reduced prevalence of SBS symptoms, whereas the state of having lower ventilation rates contributes to causing symptoms such as inflammation, respiratory infections, asthma symptoms and short-term sick leave. Additionally, sufficient use of natural ventilation (NV) systems can be also considered as a promising strategy to tackle the SBS.…”
Section: Sbs Contributors Symptoms and Effectsmentioning
confidence: 99%
“…The minimum ventilation rate was 0.5 air changes per hour, as recommended in a multidisciplinary review of literature on ventilation and health by Sendell et al based on limited data [35]. Danish regulations require exhaust capacity in kitchens and bathrooms of 20 L/s and 15 L/s respectively, so simulations assumed these maximum rates.…”
Section: Ventilation Requirementsmentioning
confidence: 99%
“…It is reported that airborne infection risk in large naturally ventilated hospital wards increases when ventilation rates decrease (Gilkeson et al 2013). Sundell et al (2011) referred that multiple health endpoints show similar relationships with ventilation rate and that there is biological plausibility for an association of health outcomes with ventilation rates. Higher ventilation rates in offices, up to about 25 L/s per person, are associated with reduced prevalence of sick building syndrome (SBS) symptoms.…”
Section: List Of Symbolsmentioning
confidence: 99%